The human body : a visual guide to human anatomy - Brewer, Sarah (London : Quercus, 2009)
'The Human Body' provides a visual explanation of the human body and how it works, using three-dimensional computer-generated images to complement the text. The book is broken down according to different body systems to give easy reference.
Includes index.
Keywords: Human body -- Popular works; Human anatomy -- Pictorial works; Human physiology -- Pictorial works; Human physiology -- Atlases